Protective Effects of Curcumin in Cardiovascular Diseases—Impact on Oxidative Stress and Mitochondria - Fiona Frederike Cox; Angelina Misiou; Annika Vierkant; Niloofar Ale-Agha; Maria Grandoch; Judith Haendeler; Joachim Altschmied (Cells, 2022)
Cardiovascular diseases (CVDs) contribute to a large part of worldwide mortality. Similarly, two of the major risk factors for these diseases, aging and obesity, are also global problems. Aging, the gradual decline of body functions, is non-modifiable. Obesity, a modifiable risk factor for CVDs, also predisposes to type 2 diabetes mellitus (T2DM). Moreover, it affects not only the vasculature and the heart but also specific fat depots, which themselves have a major impact on the development and progression of CVDs. Common denominators of aging, obesity, and T2DM include oxidative stress, mitochondrial dysfunction, metabolic abnormalities such as altered lipid profiles and glucose metabolism, and inflammation. Several plant substances such as curcumin, the major active compound in turmeric root, have been used for a long time in traditional medicine and for the treatment of CVDs. Newer mechanistic, animal, and human studies provide evidence that curcumin has pleiotropic effects and attenuates numerous parameters which contribute to an increased risk for CVDs in aging as well as in obesity. Thus, curcumin as a nutraceutical could hold promise in the prevention of CVDs, but more standardized clinical trials are required to fully unravel its potential.